HMG‐CoA reductase inhibitors (statins) and acute kidney injury: A secondary analysis of renal study outcomes. Issue 9 (27th May 2019) - Wang, Amanda Y; Trongtrakul, Konlawij; Bellomo, Rinaldo; Li, Qiang; Cass, Alan; Gallagher, Martin
ABSTRACT: Background: Mortality in intensive care unit (ICU) patients with acute kidney injury (AKI) remains high. Previous studies have explored the role of HMG‐CoA reductase inhibitors (statins) with variable findings. Methods: The Randomized Evaluation of Normal versus Augmented Level Replacement Therapy (RENAL) Study recruited 1508 participants requiring dialysis in ICU between 2006 and 2009. Statin use was recorded at study baseline. Multivariate Cox modelling was used to assess associations of such statin use and all‐cause mortality. Propensity score analysis was performed for sensitivity analysis. The primary outcome was all‐cause mortality at 90 days. Results: Of the 1462 participants with the available data on statin usage, 187 (12.8%) received statin therapy at baseline. Participants who receiving statins were older ( P < 0.001), less likely to have sepsis or require mechanical ventilation ( P < 0.001). Multivariable analysis showed statin use did not have significant associations with mortality at both day 28 (hazard ratio (HR) = 1.053, 95% confidence interval (CI) = 0.784–1.415, P = 0.730) and day 90 (HR = 1.091, 95% CI = 0.836–1.424, P = 0.520). Propensity score analysis confirmed the lack of association between statin use and mortality at day 90 (HR = 1.042, 95% CI = 0.734–1.479, P = 0.819). However, in septic patients, multivariable analysis suggested statin therapy was associated with a trend to higher mortality at day 90 (HR = 1.688, 95% CI = 1.132–2.519, P = 0.010) and continuation of statins was associated with higher mortality (HR = 2.160, 95% CI = 1.296–3.599, P = 0.003), compared with statin withdrawal. Conclusion: In the RENAL study cohort, baseline statin use was not associated with mortality. Our findings do not support a protective role of statins in ICU patients with severe AKI. Clinical Trials registration number for the RENAL study: NCT00221013, the date of registration: September 14, 2005. SUMMARY AT A GLANCE: Among 1, 462 patients requiring dialysis in the intensive care unit (ICU) between 2006 and 2009, there was no association between statin therapy and mortality. However, among patients with septic acute kidney injury (AKI) requiring dialysis, baseline statin use correlates with increased mortality. These findings do not support a protective role of statins in ICU patients with severe AKI, but raise caution about statin use among patients with septic AKI.